Private investment in agricultural research and technology transfer in Africa - Pray, Carl E.; Gisselquist, David; Nagarajan, Latha (International Food Policy Research Institute, 2011)
This study is based on surveys of private-sector innovation and research in Kenya, Senegal, South Africa, Tanzania, and Zambia in 2009 and 2010. With the exception of South Africa, Private R&D in Sub-Saharan Africa is still limited, but it is growing rapidly in several countries and is concentrated in the seed industry. The study found that innovations in plant varieties, machinery, pesticides, fertilizers, and poultry imported by private agribusiness have been important sources of new agricultural technology. A search of the literature shows that private technology increased agricultural productivity in Africa. The adoption of proprietary hybrids of maize increased yields in Tanzania. Modern poultry technology increased poultry productivity in Nigeria, and private sugarcane research in South Africa increased productivity there. Many studies show that proprietary genetically modified maize and cotton improved the yields, incomes, and health of smallholder farmers in South Africa and Burkina Faso.